The Importance of Hyaline Membrane Disease in Medicolegal Autopsies Case Report - Koyutürk, Sülbiye; Özaslan, Abdi; Koç, Sermet; Özaslan, İnci Alıç; Sarı, Hüseyin (The Bulletin of Legal Medicine, 1998)
HMD, a frequent cause of perinatal death, is of paramount importance in medicolegal autopsies, because it indicates live birth. In this paper, a case is presented which died after two days of hospitalization following birth and in which HMD was diagnosed histopathologically during autopsy.Key Words: Perinatal death, Hyalen membran disease, Live birth, Medicolegal autopsy.
Keywords: perinatal death; hyalen membran disease; live birth; medicolegal autopsy